If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7j + 2 = 3 Reorder the terms: 2 + 7j = 3 Solving 2 + 7j = 3 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 7j = 3 + -2 Combine like terms: 2 + -2 = 0 0 + 7j = 3 + -2 7j = 3 + -2 Combine like terms: 3 + -2 = 1 7j = 1 Divide each side by '7'. j = 0.1428571429 Simplifying j = 0.1428571429
| -6-9+17q=19q+11 | | 5.77x+1=33.2929+x | | S=54-.08(54) | | F(u)=u^3-10 | | .4x=-.8+2 | | 3-9k-19=-7-10k | | 15+u-22=9(2) | | 6x+35=59 | | -4s--8=142 | | 9x-7-2x=56 | | -4t-15+8t=2t+19 | | 3x+7+2x-1=11 | | 7.8+6=23.16 | | 7.8+6=23.16 | | 126+22+4x=180 | | 6x-15=x+5(3+x) | | (x+3)(x+3)=8x | | 20-16y=-19-19y | | p+4b=120 | | 2x+x+(x+2)=30 | | -208=-21x+212 | | -11-22=33 | | 7(4x-5)-4(6x-5)=-91 | | -2j-20=8j | | 8z=122 | | 65+90+5x=180 | | -3-y-X=0 | | 2x-8=-8x-24 | | 2(4-9w)= | | 57+51+9x=180 | | 6(-2y-16)-2y=-12 | | 6p+b=144 |